Економічне управління бізнесом: маркетинговий аспект - Ларка, Людмила Сергіївна; Анічкіна, Ірина Олександрівна (My University, 2019)
Визначено, що точність та достовірність прогнозів цільового рівня прибутковості бізнесу суттєво підвищується при урахуванні маркетингових аспектів, в тому числі питань стратегічного маркетингу та елементів комплексу маркетингу. Систематизовано ключові показники ефективності економічного управління бізнесом за типами бізнес-процесів. Модель управління бізнесом з акцентом на маркетингову складову представлено як сукупність блоків управлінських, операційних та підтримуючих бізнес-процесів. Зміст управлінських бізнес-процесів розкрито за рівнями стратегічного управління: корпоративна, стратегія бізнесу, функціональна та операційна стратегії. Маркетингові аспекти ураховуються в управлінських та операційних бізнес-процесах.

It was determined that the accuracy and reliability of forecasts of the target level of business profitability significantly increases when considering marketing aspects, including questions of strategic marketing and elements of the marketing mix. The purpose of this study is to systematize scientific and methodological approaches to economic management of business taking into account marketing aspects and develop a model of business economic management with the definition of key indicators of the efficiency of key business processes. Key performance indicators of economic business management by type of business processes are systematized. The business management model with an emphasis on the marketing component is presented as a set of blocks of management, operational and supporting business processes. The content of management business processes is disclosed by the levels of strategic management: corporate, business strategy, functional and operational strategies. Key indicators of the effectiveness of business processes in the model of business economic management should be logically linked to the levels of strategic management. That is why we offer the following key indicators of the effectiveness of management business processes: net profit, the value of the Spierman correlation coefficient (optimal value greater than 0.6), target market share, degree of achievement of corporate goals. Key performance indicators for operational business processes are accuracy of supply, effectiveness of price policy, efficiency of commodity policy, efficiency of marketing policy, efficiency of communication policy, the extent to which the target audience reaches. Key indicators of the effectiveness of supporting business processes can be the timely submission of financial statements to the relevant authorities, the complexity and transparency of the document circulation, the level of staff turnover and degree of satisfaction with the team working conditions. Marketing aspects are taken into account in management and operational business processes.
Economic management by business: marketing aspect
Keywords: бізнес-процес; показники ефективності; стратегія; маркетинг; управління; business process; performance indicator; strategy; marketing; management